Can phonological descriptions be made more realistic? - Rischel, Jørgen (Annual Report of the Institute of Phonetics University of Copenhagen, 1977)
This is an informal presentation of some reflections on current phonological theory, with special reference to notions such as "psychological reality", "productivity", and "naturalness".